Differences in activity patterns between adult and U-21 major league players - Harel, U.; Gershgoren, L.; Carmeli, E. (The Sport Journal, 2020)
The purpose of this study was to measure differences in activity patterns between major league adult and U-21 soccer players. Four U-21 players and four adult team players were evaluated using a repeated measures technique. All eight players were affiliated with the Maccabi Haifa Soccer Club from the Israeli professional and U-21 major leagues, depending on the player`s age. GPS sensors were attached to the players during five consecutive games to identify patterns regarding running distance and speed according to the field positions. There was no significant difference in the total running distances covered by two age groups; however, when measuring high running speed, an advantage was observed for the adult group in comparison to the U-21 in general and between players playing in the same position. These findings provide valuable knowledge that may serve the principle of training specificity. First, it may assist practitioners adjust specific intensity levels to players depending on their position on the field and physical function. Moreover, it can serve coaches in transitioning U-21 players to the adult team by progressively adjusting their physical capacities to those needed at the adult level.